Daily Video: A tool for quality of experience (QoE) in long-term context research - Jarosław Bułat; Natalia Cieplińska; Rafał Figlus; Lucjan Janowski (SoftwareX, 2024)
This paper presents ‘Daily Video’, an innovative application designed to facilitate longitudinal studies in the realm of quality of experience (QoE). The application simulates real-life video service consumption and collects daily subjective quality assessments from users, promoting an in-depth understanding of user engagement and habits over time. Key features include scheduling, customised queries, user feedback, device orientation tracking and instant access to results, all of which enhance the application’s adaptability and usability for a variety of experimental conditions. The application, available as open-source code, supports state-of-the-art QoE research.